Siddiqui, Ali. “The Global Intellectual Crisis: Towards an Alternative Qur’anic Epistemological Model,” Year 15, Issue 59 (Winter 1431 AH/ 2010 CE), Pp. 25- 58. - صديقي, علي (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma'rifah), 2010)
Ali Siddiqui’s article addresses dialogue and acquaintance between civilizations, and the conditions of its success by endorsing two necessary principles: the default in dialogue is difference, and the default in acquaintance is recognition and exchange of knowledge. It then discusses the most important dilemmas of the Western epistemological model, represented in its dependence on a material frame of reference and exclusion of metaphysics. The article envisions what an alternative model based on the foundation of tawḥīd (Oneness of God) would be like. It concludes with an emphasis on the importance of Islamization of knowledge in civilizational dialogue and acculturation with the different epistemological patterns and intellectual models. The article addresses the dilemmas of the modern epistemological model, features of the alternative epistemological model, presenting an alternative model, and striving to ensure its spread, means of overcoming self-obstacles related to the Muslim Ummah itself, and the objectivity associated with the Western world.